Intentional Action, Know-how, and Lucky Success - Michael Kirley (Ergo, An Open Access Journal of Philosophy)
Elizabeth Anscombe held that acting intentionally entails knowing (in a distinctively practical way) what one is doing. The consensus for many years was that this knowledge thesis faces decisive counterexamples, the most famous being Donald Davidson’s carbon copier case, and so should be rejected or at least significantly weakened. Recently, however, a new defense of the knowledge thesis has emerged: provided one understands the knowledge in question as a form of progressive judgement, cases like Davidson’s pose no threat. In this paper, I argue that this neo-Anscombean maneuver fails because it is founded on an untenable conception of the difference between intentional and merely lucky success. More specifically, the neo-Anscombean view conflates merely lucky success with subjectively surprising success. Unlike the former, subjectively surprising success may well be intentional, for it may well be the result of an exercise of knowledge-how. After sketching an alternative view that better captures the intuitive contrast between lucky and intentional success, I argue that the conflation of surprising and merely lucky success owes to a tacit commitment to the thesis that knowing how entails knowing that one knows how. This thesis is not only false, but distortive of the explanatory role of knowledge-how. This result, in turn, tells us something important about what practical knowledge cannot be.